2021
DOI: 10.1111/ddi.13252
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the reliability of species distribution projections in climate change research

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
129
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(133 citation statements)
references
References 111 publications
(178 reference statements)
3
129
1
Order By: Relevance
“…Our models also suggested that the widespread Brazilian peppertree ( Schinus terebinthifolia ) may lose up to 47% of its original habitats. These results need to be interpreted with caution, since all species that were predicted to lose 100% of BAH have small sample sizes (n < 50, Supplementary Table S1 ), which is one of the main determinants of model accuracy 51 . Some species tend to be favored by certain climate change scenarios under full dispersal scenario 52 , 53 , such as here the medicinal species Varronia curassavica , with an increase of BAH up to 230%; the ornamental species Epidendrum fulgens up to 264% and the forage species Indigofera sabulicola up to 387%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our models also suggested that the widespread Brazilian peppertree ( Schinus terebinthifolia ) may lose up to 47% of its original habitats. These results need to be interpreted with caution, since all species that were predicted to lose 100% of BAH have small sample sizes (n < 50, Supplementary Table S1 ), which is one of the main determinants of model accuracy 51 . Some species tend to be favored by certain climate change scenarios under full dispersal scenario 52 , 53 , such as here the medicinal species Varronia curassavica , with an increase of BAH up to 230%; the ornamental species Epidendrum fulgens up to 264% and the forage species Indigofera sabulicola up to 387%.…”
Section: Discussionmentioning
confidence: 99%
“…ENMs are widely used to forecast the distribution of species across geographic space and time. Building meaningful models to estimate the future distribution of species for an uncertain future requires very specific decisions and interpretations with extreme caution 51 , 77 , 78 . Several uncertainties and complexities are related to our study.…”
Section: Discussionmentioning
confidence: 99%
“…the conversion of water availability to respiration via specific leaf area, and of temperature to metabolism via wood density and height), therefore reducing the risk of establishing spurious relationships (e.g. Fourcade et al., 2018; Santini et al., 2021). Assuming that these models capture the causal relationships between climate and community mean trait values, the relationships are in principle transferable to future scenarios (Dormann et al., 2012; Yang et al., 2016, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In our case these two metrics revealed good results. However, discrimination accuracy metrics may suggest a very good model while of poor transferability (Torres et al, 2015) and/or lead to relationships without a biological meaning (Santini et al, 2021). Using only Ukrainian-based records, we tested our models by extrapolating predictions of occurrence and habitat suitability to neighbouring areas, for instance to Krasnodar Province of the Russian Federation (Fig.…”
Section: Discussionmentioning
confidence: 99%